E-learning through Google Hangouts: a tool in the teaching-learning process of EFL - Fernández Sánchez, Higinio; Enríquez Hernández, Claudia B.; Fernández, Blanca Flor; Martínez Díaz, Nazaria; Santes Bastian, María del Carmen (Acta Universitaria, 2019)
As today’s world becomes a networked society, Information and Communication Technologies (ICT) have become powerful contributors towards the acquisition of a foreign language. The aim of this study is to examine the feasibility of implementing a technology-based program: the English as a Foreign Language (EFL) students’ satisfaction with the program and the perceived benefits in improving their English skills (speaking, listening, reading, and writing). A one-group, pretest-posttest design was used. A six-week technology-based program, with 30 min sessions, was implemented once a week. A total sample size of 20 students enrolled in a one-day advanced EFL course. There was a high satisfaction towards the program (80%) and towards the facilitator (100%). Fifty percent of participants considered the Hangout sessions as very helpful in developing their speaking skill, 75% considered them to be very helpful for their listening skill., and 50% reported the Hangout sessions to be somewhat helpful in developing their reading skill and their writing skill. Even though taking time to work outside of the classroom had its challenges, the virtual environment led to the collaboration between students, who demonstrated high commitment during the sessions, allowing their writing, reading, speaking and listening skills to improve.